2017
DOI: 10.1038/ncomms15663
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-binding cassette transporter A1 regulates phosphoantigen release and Vγ9Vδ2 T cell activation by dendritic cells

Abstract: Vγ9Vδ2 T cells are activated by phosphoantigens, such as isopentenyl pyrophosphate (IPP), which is generated in the mevalonate pathway of antigen-presenting cells. IPP is released in the extracellular microenvironment via unknown mechanisms. Here we show that the ATP-binding cassette transporter A1 (ABCA1) mediates extracellular IPP release from dendritic cells (DC) in cooperation with apolipoprotein A-I (apoA-I) and butyrophilin-3A1. IPP concentrations in the supernatants are sufficient to induce Vγ9Vδ2 T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 54 publications
1
82
0
Order By: Relevance
“…While cell lysis could still play a role in the "export" of IPP, follow-up analysis indicated that IPP is transported, or at least taken-up, by the engineered E. coli DH1 used in this study ( Figure 5). Recent work in mammalian dendritic cells showed that ATP-binding cassette transporter A1 (ABCA1) plays a role in extracellular IPP release (Castella et al, 2017). Several ABC transporters with homology to ABCA1 such as MetN were upregulated in strain 3Amk, though we are unable to link any of these transporters with IPP efflux with the current data set (Supplemental File S2, Jupyter R notebook "IPP_transcriptomics").…”
Section: Discussionmentioning
confidence: 64%
“…While cell lysis could still play a role in the "export" of IPP, follow-up analysis indicated that IPP is transported, or at least taken-up, by the engineered E. coli DH1 used in this study ( Figure 5). Recent work in mammalian dendritic cells showed that ATP-binding cassette transporter A1 (ABCA1) plays a role in extracellular IPP release (Castella et al, 2017). Several ABC transporters with homology to ABCA1 such as MetN were upregulated in strain 3Amk, though we are unable to link any of these transporters with IPP efflux with the current data set (Supplemental File S2, Jupyter R notebook "IPP_transcriptomics").…”
Section: Discussionmentioning
confidence: 64%
“…All data in the text and figures are provided as means ± SD. The results were analyzed by a one-way analysis of variance (ANOVA), using the Statistical Package for Social Science (SPSS) software (IBM SPSS Statistics v. 19). p < 0.05 was considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we focused on a recently-discovered function of ABCA1, i.e., the efflux of the isoprenoid metabolite IPP that activates Vγ9Vδ2 T-cells [19], a subset of T-lymphocytes with potential killing activity against transformed cells that act also when αβ T-cell-mediated immunity is impaired [11,12,14]. Our gain-and loss-of-function experiments provided the demonstration that ABCA1 transports IPP and modulates the activity of Vγ9Vδ2 T-lymphocytes in osteosarcoma, as it does in antigen-presenting cells [19]. Moreover, we report for the first time a new chemo-immune-resistant phenotype, based on the simultaneous up-regulation of ABCB1 and down-regulation of ABCA1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations